2015
DOI: 10.1111/resp.12558
|View full text |Cite
|
Sign up to set email alerts
|

Increases in peripheral SIRT1: A new biological characteristic of asthma

Abstract: Background and objective: Silent information regulator 1 (SIRT1) is a class III histone deacetylase that exerts both anti-inflammatory and anti-aging effects. However, no data are available regarding SIRT1 expression in patients with asthma. Here, we studied SIRT1 levels in the serum of patients with asthma and analysed the distribution of SIRT1 in both the serum and the lungs in an asthmatic mouse model to determine its clinical significance. Methods: Serum SIRT1 levels, total immunoglobulin E (IgE) levels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 31 publications
(36 reference statements)
5
35
2
1
Order By: Relevance
“…46 Serum SIRT1 levels were found to be significantly elevated in asthmatic patients, positively correlated with total IgE levels and negatively correlated with pulmonary function. 47 Also reported in Respirology, an increased serum SIRT1 level was confirmed in murine model of asthma, whereas decreased SIRT1 expression was observed in mouse lung tissue, similar to a previous study. 48 These findings suggest that high levels of serum SIRT1 are a biological characteristic of asthma and elevating lung SIRT1 levels with activators may be a new strategy for asthma therapy.…”
Section: Airway Inflammationsupporting
confidence: 89%
See 1 more Smart Citation
“…46 Serum SIRT1 levels were found to be significantly elevated in asthmatic patients, positively correlated with total IgE levels and negatively correlated with pulmonary function. 47 Also reported in Respirology, an increased serum SIRT1 level was confirmed in murine model of asthma, whereas decreased SIRT1 expression was observed in mouse lung tissue, similar to a previous study. 48 These findings suggest that high levels of serum SIRT1 are a biological characteristic of asthma and elevating lung SIRT1 levels with activators may be a new strategy for asthma therapy.…”
Section: Airway Inflammationsupporting
confidence: 89%
“…Sirtuin 1 (SIRT1), a member of the silent information regulator 2 family, belongs to class III histone deacetylase and is associated with airway inflammation and hyperresponsiveness in allergic asthma . Serum SIRT1 levels were found to be significantly elevated in asthmatic patients, positively correlated with total IgE levels and negatively correlated with pulmonary function . Also reported in Respirology , an increased serum SIRT1 level was confirmed in murine model of asthma, whereas decreased SIRT1 expression was observed in mouse lung tissue, similar to a previous study .…”
Section: Asthmasupporting
confidence: 85%
“…Moreover, they found that treatment of OVA mice with a SIRT1 activator decreased inflammatory cell lung infiltrates and IL-5 and IL-13 levels in the BAL fluid compared to those in the vehicle treatment [6] , which indicated the anti-inflammation effects of SIRT1. In addition, Wang et al also confirmed decreased SIRT1 expression in the lung tissues of OVA mice [7]. In asthma patients, Colley et al found SIRT1 activity was decreased in PBMCs from patients with severe asthma when compared to healthy subjects, and loss of SIRT1 activity increases IL-4 expression in patients with severe asthma [8].…”
Section: Introductionmentioning
confidence: 77%
“…Spirometry was measured using standard spirometric techniques (POS Instrumentation, Inc., Louisville USA) according to the American Thoracic Society (ATS) guidelines as we previously described (Wang et al, 2015).…”
Section: Pulmonary Function Testsmentioning
confidence: 99%